2022
DOI: 10.1016/j.jjcc.2021.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mitral versus aortic bioprosthetic valve position on thromboembolism and bleeding risk in patients with atrial fibrillation

Abstract: Background:The impact of valve position on thromboembolic and bleeding events in patients with atrial fibrillation (AF) and bioprosthetic valves is uncertain. Methods: We analyzed 159 patients with AF after surgical single-valve replacement from the BPV-AF registry (Retro) (UMIN0 0 0 034198), which was a multicenter, retrospective, observational registry that enrolled 214 patients with AF and bioprosthetic valves to assess differences in bioprosthetic valve position. Baseline characteristics and clinical outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…We previously evaluated the impact of mitral BPV position vs. aortic BPV position on the clinical outcomes of AF patients after surgical valve replacement with a BPV and reported that thromboembolic risk did not differ according to valve position. 24 Bleeding risk was higher in patients with a mitral BPV than in those with an aortic BPV, although valve position itself might not be an independent predictor of bleeding. 24 However, that retrospective study involved a small sample size, and further research is needed.…”
Section: Study Limitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…We previously evaluated the impact of mitral BPV position vs. aortic BPV position on the clinical outcomes of AF patients after surgical valve replacement with a BPV and reported that thromboembolic risk did not differ according to valve position. 24 Bleeding risk was higher in patients with a mitral BPV than in those with an aortic BPV, although valve position itself might not be an independent predictor of bleeding. 24 However, that retrospective study involved a small sample size, and further research is needed.…”
Section: Study Limitationsmentioning
confidence: 92%
“…24 Bleeding risk was higher in patients with a mitral BPV than in those with an aortic BPV, although valve position itself might not be an independent predictor of bleeding. 24 However, that retrospective study involved a small sample size, and further research is needed.…”
Section: Study Limitationsmentioning
confidence: 92%